Application of Learning Media to Improve Understanding of Food Chain in Elementary School Students - Nurul Agustina Ginting; Dewi Sulistianingsih; Neni Hermita; Rifqa Gusmida Syahrun Barokah (Universitas Islam Ahmad dahlan, 2025)
This study aims to describe the application of contextual learning media in enhancing students' understanding of the food chain concept at SDN 184 Pekanbaru. A qualitative descriptive approach was used with direct observation of 41 fifth-grade students. Data were collected through observation and documentation. The results showed that the use of concrete media, such as a food chain diorama, helped clarify the relationships among living organisms in an ecosystem, increased motivation, and promoted active student participation. The application of this media also fostered ecological awareness among students regarding their surrounding environment. This research is expected to contribute to the development of more effective learning media that aligns with the developmental characteristics of students. Keywords:Concrete media, contextual learning, food chain, problem based learning, kualitatif Abstrak Penelitian ini bertujuan untuk mendeskripsikan penerapan media pembelajaran kontekstual dalam meningkatkan pemahaman siswa terhadap konsep rantai makanan di SDN 184 Pekanbaru. Penelitian menggunakan pendekatan kualitatif deskriptif dengan observasi langsung terhadap 41 siswa kelas V. Data dikumpulkan melalui observasi dan dokumentasi. Hasil penelitian menunjukkan bahwa penggunaan media konkret, seperti diorama rantai makanan, mampu memperjelas hubungan antar makhluk hidup dalam ekosistem, meningkatkan motivasi, serta partisipasi aktif siswa. Penerapan media ini juga mampu membangun kesadaran ekologis siswa terhadap kondisi lingkungan sekitar. Penelitian ini diharapkan dapat memberikan kontribusi terhadap pengembangan media pembelajaran yang lebih efektif dan sesuai dengan karakteristik perkembangan siswa.